Ciclos econômicos na América Latina: uma análise da Argentina, Brasil, Chile e México no período 1950-2007 - Ness, Mosar Leandro (Universidade do Vale do Rio do Sinos, 2009)
Economic cycles represent fluctuations of variables such as production and employment in a sector, region or country. They are so unique, and not divisible with characteristics as to its magnitude and duration. In general, the cycles can be subdivided in the following phases: expansion, crisis and depression. Each phase switches to the behavior of other predetermined later. One of the most promising techniques is the model of regime change, with the seminal work of Hamilton (1989) opened up a new field of research within the theme. It is that research on economic cycles in the international literature has focused on central economies and emerging countries still have a relatively low number of jobs in the area. When compared to other continents, they have a natural context for discussions in terms of the theory of economic cycles. In this study, we used the technique of changing the Markovian regime, which in addition to univariate and multivariate formulations was tested bivariate arrangements. Because of th
Keywords: cointegração; comovimento; crise; depressão; expansão; mudança de regime; ciclo econômico; change of regime; cointegrating; crisis; depression; touched; business cycle expansion; Ciências Sociais Aplicadas